A study of enterocyte membranes during activation of apoptotic processes in chronic carrageenan–induced gastroenterocolitis - Anton Tkachenko; Dmytro Marakushyn; Iuliia Kalashnyk; Yevgen Korniyenko; Onishchenko Anatolii; Tatyana Gorbach; Oksana Nakonechna; Yevgen Posokhov; Alexander Tsygankov (Medicinski glasnik, 2018)
Aim: To investigate the lipid membranes of rat enterocytes in chronic carrageenan-induced gastroenterocolitis accompanied by the activation of apoptotic processes. Methods: Steady-state fluorescence spectroscopy: a study by fluorescent probes-by ortho-hydroxy derivatives of 2,5-diaryl-1,3oxazole. Activity of apoptosis signal-regulating kinase 1 and poly (ADP-ribose) polymerase in small intestinal homogenates, blood serum levels of matrix metalloproteinase-2 and caspase-3 and the level of DNA fragmentation in small intestinal homogenates were determined. Results: Biochemical analysis revealed that an activation of apoptotic processes occurred in the intestinal epithelium of rats during chronic carrageenan-induced gastroenterocolitis. The fluorescence probes showed that activation of apoptotic processes in carrageenan-induced gastroenterocolitis was accompanied by changes in polar regions of rat enterocyte membranes, while no changes were revealed in more hydrophobic regions of the membranes. Conclusion: The increase in hydration of membranes was attributed to the activation of the apoptosis of enterocytes. It has been shown that a fluorescent probe (2-(2′-hydroxyphenyl)-5-phenyl-1,3-oxazole) can be used for the detection of apoptosis of enterocytes.
Keywords: apoptosis; caspases; food additives; rats; inflammation